Profound degeneration of wake‐promoting neurons in Alzheimer's disease. Issue 10 (12th August 2019) - Oh, Jun; Eser, Rana A.; Ehrenberg, Alexander J.; Morales, Dulce; Petersen, Cathrine; Kudlacek, Jessica; Dunlop, Sara R.; Theofilas, Panos; Resende, Elisa D.P.F.; Cosme, Celica; Alho, Eduardo J.L.; Spina, Salvatore; et al.
Abstract: Introduction: Sleep‐wake disturbances are a common and early feature in Alzheimer's disease (AD). The impact of early tau pathology in wake‐promoting neurons (WPNs) remains unclear. Methods: We performed stereology in postmortem brains from AD individuals and healthy controls to identify quantitative differences in morphological metrics in WPNs. Progressive supranuclear palsy (PSP) and corticobasal degeneration were included as disease‐specific controls. Results: The three nuclei studied accumulate considerable amounts of tau inclusions and showed a decrease in neurotransmitter‐synthetizing neurons in AD, PSP, and corticobasal degeneration. However, substantial neuronal loss was exclusively found in AD. Discussion: WPNs are extremely vulnerable to AD but not to 4 repeat tauopathies. Considering that WPNs are involved early in AD, such degeneration should be included in the models explaining sleep‐wake disturbances in AD and considered when designing a clinical intervention. Sparing of WPNs in PSP, a condition featuring hyperinsomnia, suggest that interventions to suppress the arousal system may benefit patients with PSP.